A Randomized Controlled Trial Comparing Laser Intra-Hemorrhoidal Coagulation and Milligan–Morgan Hemorrhoidectomy. (3rd September 2017) - Naderan, Mohammad; Shoar, Saeed; Nazari, Mohammad; Elsayed, Ahmed; Mahmoodzadeh, Habibollah; Khorgami, Zhamak
ABSTRACT: Purpose : To compare laser intra-hemorrhoidal coagulation with Milligan–Morgan (MM) hemorrhoidectomy. Method : Patients with symptomatic grade II or III internal hemorrhoids according to the Goligher's classification (refractory to medical treatment) were enrolled in this double-blinded randomized controlled trial study. In the laser group, hemorrhoidal columns were coagulated using a 980-nanometer (nm) radial laser emitting fiber (three, 15-W pulses of 1.2 s each, with 0.6-s intervals). Operative time, postoperative pain and complications, and recovery or resolution of symptoms were measured. Patients were followed up for at least one year for evaluating healing, resolution of symptoms, and late complications. Results : Postoperative pain scores (at 12, 18, and 24 hr after surgery) were significantly lower in the laser group compared with the MM group ( p <.01). The operative time and intra-operative blood loss were more in the MM group ( p <.001). The administration of analgesics was significantly reduced in the laser group ( p <.05). Two patients in the laser group were presented with thrombosis of external hemorrhoid 7–10 days after the procedure, which was resolved with medical treatment, but no patients in the MM group developed hemorrhoidal thrombosis ( p >.05). One-year follow-up showed comparable results in terms of the resolution of symptoms and sustainable cure. Conclusions : Intra-hemorrhoidal coagulation with 980-nm diode laser reduces postoperative pain, intra-operative bleeding, and administered analgesics with a comparable resolution rate of hemorrhoid symptoms. However, for the patients who experience complications, such as hemorrhoidal thrombosis, the overall pain may be equivalent to or even worse than conventional hemorrhoidectomy.